Survey study of lead exposure among lead workers in Erbil - Ansam Naji Al-Hassani (University of Mosul, 2013)
Objectives: The aim of this work was to assess lead contamination among lead workers in Erbil city. Patients and methods: This study was carried out on male people working in printing press (30 workers), radiator repairing (26 workers), battery repairing (26 workers), and gasoline power generator (25 wokers), compared with control group (30 males). Results: Blood lead levels significantly increased in printing press workers (P